Pengembangan Bahan Ajar Buku Bacaan Pada Tema VII Sub Tema 2 Anak SD Kelas VI Berbantuan Aplikasi Pinterest Sebagai Design Di SDN 066664 Medan - Sri Ningsih; Husna Parluhutan Tambunan (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
The problem in this study is the lack of teaching materials in SDN 066664 Medan which supports the learning process in addition to reading books from Ministry of Education and Culture where this will have an impact on students and also teachers. Teacher will experience difficulties in increasing the effectiveness of learning and students will having difficulty learning. The purpose of this research is to determine the feasibility, practicality, and effectiveness of developing book teaching materials reading on Theme 7 sub-theme 2 in Class VI SD Negeri 066664 Medan. This research using research methods R & D (Research and Development) which will produce a particular product and see the effectiveness of the product. This research using the ADDIE development model according to A.Personal (2014), namely Analysis, Design, Development, Implementation (Implementation), and Evaluation (Evaluation). The subjects of this study were students of class VI SD Negeri 066664 Medan has a total of 27 students with 13 male students and 14 female students. Woman. The data analysis technique in this study is quantitative data obtained from the average score of the questionnaire from material experts, validation experts, and practicing experts adjusted to the guidelines for scoring each aspect and then converted into qualitative criteria. The results of the research show the feasibility of obtaining the material assessment with a percentage of 91.6% and is in the "very decent" category. The percentage score obtained for design feasibility validation is 92.8% with the category of "very feasible". It can be concluded that the teaching material products that have validated for use. In the practicality test obtained a percentage of 96% which means it is already in the category "Very Practical" which means reading book material that has been developed for practical use in class VI students of public elementary schools 066664 Medan. In the effectiveness test, tests were used, namely the pre-test and the final test (post-test). The results of the pre-test pre-test obtained an average of 63.33% of students then carried out post-test obtained an average student score of 96.66%. From these results it can be concluded that student learning outcomes have increased from the pre-test to post-test and teaching materials that have been developed are effective in learning Theme VII Sub-theme 2 Class VI at SDN 066664 Medan.